2012
DOI: 10.1038/nbt.2137
|View full text |Cite
|
Sign up to set email alerts
|

Systematic dissection and optimization of inducible enhancers in human cells using a massively parallel reporter assay

Abstract: Learning to read and write the transcriptional regulatory code is of central importance to progress in genetic analysis and engineering. Here, we describe a massively parallel reporter assay (MPRA) that enables systematic dissection of transcriptional regulatory elements by integrating microarray-based DNA synthesis and high-throughput tag sequencing. We apply MPRA to compare more than 27,000 distinct variants of two inducible enhancers in human cells: a synthetic cAMP-regulated enhancer and the virus-inducibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
656
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 632 publications
(679 citation statements)
references
References 29 publications
19
656
2
2
Order By: Relevance
“…1C). We cloned these 3,000 sequences ("candidate enhancers") into plasmids containing a minimal promoter and an ORF containing a unique barcode that identifies its specific upstream enhancer (48). We transfected this plasmid pool into mouse 3T3-L1 adipocytes 7 d postdifferentiation; grew the cells for 16 h; and measured PPARγ binding by performing ChIP-seq and calculating the relative enrichment of reads corresponding to each sequence.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1C). We cloned these 3,000 sequences ("candidate enhancers") into plasmids containing a minimal promoter and an ORF containing a unique barcode that identifies its specific upstream enhancer (48). We transfected this plasmid pool into mouse 3T3-L1 adipocytes 7 d postdifferentiation; grew the cells for 16 h; and measured PPARγ binding by performing ChIP-seq and calculating the relative enrichment of reads corresponding to each sequence.…”
Section: Resultsmentioning
confidence: 99%
“…Oligonucleotide libraries containing the 145-or 150-bp candidate enhancers were synthesized (Agilent Technologies) and unique barcodes were added by PCR. The oligonucleotide libraries were cloned into a plasmid backbone with a minP-luc2 insert, as previously described (48,95).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We, and others before us, have shown that massively parallel enhancer-reporter assays can relatively quickly lead to such training sets, and usually lead to exciting new insight into the cis-regulatory logic of enhancers (Kwasnieski et al 2012;Melnikov et al 2012;Arnold et al 2013;Kheradpour et al 2013;White et al 2013). In our study, we tested long enhancer sequences, of several hundreds of base pairs.…”
Section: Tp53 Enhancer Logicmentioning
confidence: 99%
“…Whereas classically enhancer-reporter assays consist of cloning each enhancer one by one, first in vitro, later in vivo (Banerji et al 1981;O'Kane and Gehring 1987;Chiocchetti et al 1997;Dailey 2015), now hundreds to thousands of enhancers can be tested in parallel (Patwardhan et al 2009(Patwardhan et al , 2012Kwasnieski et al 2012;Melnikov et al 2012;Arnold et al 2013;Kheradpour et al 2013;Smith et al 2013;White et al 2013;Vanhille et al 2015). These methods can be broadly categorized in two groups, namely, massively parallel reporter assays (MPRA) utilizing barcodes as a measure of activity of synthesized enhancer fragments (Patwardhan et al 2009(Patwardhan et al , 2012Kwasnieski et al 2012;Melnikov et al 2012;Kheradpour et al 2013;Smith et al 2013;White et al 2013) and self-transcribing active regulatory region sequencing (STARR-seq) (Arnold et al 2013;Vanhille et al 2015).…”
mentioning
confidence: 99%